Authority of State Institutions in Establishing Laws Under the Constitution of the Democratic Republic of Timor-Leste - Lourenco de Deus Mau Lulo; I Gusti Ngurah Wairocana; I Wayan Parsa; I Nyoman Suyatna (International Journal of Educational and Life Sciences, 2023)
This dissertation discusses the authority of state institutions in forming laws based on the Constitution of the Democratic Republic of Timor-Leste (RDTL). With regard to the division of powers of state institutions in the 2002 RDTL Constitution, there are many interpretations, because the phrase "must be based on the principle of separation of powers, and "interdependence" which leads to separation and division of powers. Authority The legal materials used in the research and writing of this dissertation consist of primary legal materials, secondary legal materials, and tertiary legal materials. The results of this research can be summarized as follows: Philosophical considerations on the division of authority of state institutions in the Constitution of the Democratic Republic of Timor-Leste The basis for consideration by the 2002 Constituent Assembly which permitted the Government to form laws. The implementation of the proposed draft licensing law depends on: a) The term of office of the legislature. b) Term of office of the Government. c) the draft law on legislative permits proposed.